Urologic Cancers - Barber, Neil; Ali, Ahmed (Exon Publications, 2022)
Urologic cancers are an umbrella term for cancers of the prostate, kidney, bladder, penis, and testis. Routine use of advanced imaging modalities for various reasons has increased the incidental detection of some of these cancers at an early stage. Robot-assisted surgery for nephrectomy, prostatectomy, cystectomy, and retroperitoneal lymph node dissection have improved surgical outcomes of localized disease. The introduction of targeted therapies since 2006 has revolutionized the management of metastatic kidney cancer. Despite these advances, the five-year survival of patients with advanced renal cancer is still poor and we need a better understanding of the disease. The book Urologic Cancers brings together an international team of clinicians and basic scientists to provide an up-to-date overview of a wide spectrum of topics that comprise epidemiological, pathological, clinical, and biological aspects of urologic cancers. From the epidemiological spectrum, the most recent information on the epidemiology of testicular cancer and penile cancer are presented. From the clinical spectrum, the characteristics and management of divergent urothelial neoplasms, the role of surgery in the management of testicular and kidney cancer, biopsy approaches for better detection and diagnosis of prostate cancer, the role of family history and germline genetics in prostate cancer disease profiling and screening, and the need for the implementation of quality assurance programs to improve prostate cancer care discussed. The biological aspects of disease mechanisms focus on various emerging molecular pathways and how these can be targeted to develop novel therapeutics. The contents of the book will be of interest to healthcare professionals, basic scientists and clinicians interested in urologic cancers.